Thalamic Iron Differentiates Primary-Progressive and Relapsing-Remitting Multiple Sclerosis - Burgetova, A.; Dusek, P.; Vaneckova, M.; Horakova, D.; Langkammer, C.; Krasensky, J.; Sobisek, L.; Matras, P.; Masek, M.; Seidl, Z. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Potential differences between primary progressive and relapsing remitting multiple sclerosis are the subject of ongoing controversial discussions. The aim of this work was to determine whether and how primary-progressive and relapsing-remitting multiple sclerosis subtypes differ regarding conventional MR imaging parameters, cerebral iron deposits, and their association with clinical status.MATERIALS AND METHODS: We analyzed 24 patients with primary-progressive MS, 80 with relapsing-remitting MS, and 20 healthy controls with 1.5T MR imaging for assessment of the conventional quantitative parameters: T2 lesion load, T1 lesion load, brain parenchymal fraction, and corpus callosum volume. Quantitative susceptibility mapping was performed to estimate iron concentration in the deep gray matter.RESULTS: Decreased susceptibility within the thalamus in relapsing-remitting MS compared with primary-progressive MS was the only significant MR imaging difference between these MS subtypes. In the relapsing-remitting MS subgroup, the Expanded Disability Status Scale score was positively associated with conventional parameters reflecting white matter lesions and brain atrophy and with iron in the putamen and caudate nucleus. A positive association with putaminal iron and the Expanded Disability Status Scale score was found in primary-progressive MS.CONCLUSIONS: Susceptibility in the thalamus might provide additional support for the differentiation between primary-progressive and relapsing-remitting MS. That the Expanded Disability Status Scale score was associated with conventional MR imaging parameters and iron concentrations in several deep gray matter regions in relapsing-remitting MS, while only a weak association with putaminal iron was observed in primary-progressive MS suggests different driving forces of disability in these MS subtypes.BPFbrain parenchymal fractionCCVcorpus callosum volumeCNcaudate nucleusDGMdeep gray matterEDSSExpanded Disability Status ScaleGPglobus pallidusHChealthy controlsPutputamenQSquantitative susceptibilityQSMquantitative susceptibility mappingPPMSprimary-progressive multiple sclerosisRRMSrelapsing-remitting multiple sclerosisRREMrelapsing-remitting EDSS-matched groupT1LLT1 lesion loadT2LLT2 lesion load